EFEKTIVITAS MEDIA PEMBELAJARAN MATEMATIKA BERBASIS ANDROID DITINJAU DARI KEMAMPUAN KOMUNIKASI MATEMATIS DAN RASA INGIN TAHU PESERTA DIDIK SEKOLAH DASAR - Arifin, Nurdin; Qomariah, Annisa; Tunru, Andi Alif; Pertiwi, Indah; Fauziah, Putri Dian; Wahyuningrum, Retno (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The development of digital technology has brought significant changes to the field of education, including mathematics learning. This study aimed to examine the effectiveness of Android-based learning media in improving students' mathematical communication skills and curiosity. The research was conducted in Class V A of SDN 027 Samarinda Ulu during the 2024/2025 academic year, using a quasi-experimental pretest-posttest design. Data were collected through tests and questionnaires, then analyzed. The normality test results indicated that the data were normally distributed. The homogeneity test showed that the data were homogeneously distributed. The one-sample t-test and proportion test revealed that the average score of students' mathematical communication exceeded the minimum threshold of 70, and more than 75% of students reached this score, placing them in the “good” category. Meanwhile, the paired-sample t-test showed a significant increase in students’ curiosity after the learning intervention, and the one-sample t-test showed that the final curiosity scores exceeded the benchmark of 73.41. The use of Android-based learning media proved to be effective in developing mathematical communication skills and fostering students’ curiosity. These findings reinforce the importance of integrating technology into the learning process to create an active, meaningful, and enjoyable learning environment.